Constitutional and legal adjusting of national security in Ukraine - Drobotov, Serhii (ScienceRise: Juridical Science, 2020)
The essence and political-legal nature of constitutional-legal provision of national security in Ukraine are revealed. The role of the Constitution of Ukraine in the process of ensuring national interests and the formation of a security environment has been studied. An analysis of the system-forming and organizational and constituent function of the Constitution of Ukraine in this area has been carried out. The main content of the constitutional and legal provision of national security in Ukraine is disclosed. A study has been carried out of the main provisions of the Constitution and the laws of Ukraine in the field of establishing the foundations for the implementation of national security. An analysis of the provisions of the Constitution of Ukraine has been carried out with a view to consolidating and regulating certain principles of the functioning of the national security system of Ukraine. The basic principles of constitutional and legal regulation of the organizational and institutional component of the national security system are defined. The special State legal nature of the Constitution of Ukraine as a central element in the organization of national security was studied. The Constitution of Ukraine contains provisions of a predominantly general nature, which determine the system of guarantees of human and civil rights and freedoms, determine the foundations and priorities of the national security policy, and it is its provisions that ensure the unity of architects and organizational coherence of the existence of the national security system of Ukraine. At the same time, there is a significant lack of constitutional and legal regulation in this area. In particular, the Constitution of Ukraine (arts. 17-18) defines the obligation of participation of society and citizens of Ukraine in ensuring only certain components of national security: information, economic, military. In other areas, such participation is not a constitutional and legal obligation of citizens. In addition, the very concept and content of the "national security" category should be enshrined at the constitutional level, and the Constitution of Ukraine should not have a dichotomy of the "national" and "state" security categories, which contains risks of reducing the effectiveness of the entire system of its practical provision